Talent identification in youth football: A systematic review - Mustafovic, E.; Causevic, D.; Covic, N.; Ibrahimovic, M.; Alic, H.; Abazovic, E.; Masic, S. (Journal of Anthropology of Sport and Physical Education, 2020)
Identification of talents in football is one of the most important tasks of coaches in youth football selection. The main focus of this paper was to review the available literature on talent identification in youth football. A systematic review of PubMEd, Medline, ResearchGate and Elsevier databases was performed according to PRISMA guidelines. The following keywords were used: "identification of talents", "football talent", "selection in football", and "management in sport clubs". Of 137 studies initially identified, of which 17 met the inclusion criteria of the review. Mentioned studies were analyzed and discussion was created with the emphasis on 4 segments: 1) analysis of physiological aspects and identification of talents 2) importance of specific contents for identification of talent 3) biological and chronological age as an important aspect of selection of young players 4) multidisciplinary approach to the selection of young players. It is concluded that process of identification of talents needs to be approached multidisciplinary with all contents of physiological and physical assessment and with specific football contents (SSG and TE-TA contents) respectively. Great role in performance on the field has the biological age, on which coaches need to pay attention to when evaluating quality of players.